Village Apparatus Competence, Community Participation, and BPD Supervision on Village Fund Management Effectiveness - Amanda Devi Mutiara; Eksa Ridwansyah; Evi Yuniarti (Goodwood Publishing, 2026)
Purpose: This study examines the effects of village apparatus competence, community participation, and Village Consultative Body (BPD) supervision on village fund management effectiveness in Meraksa Aji Sub-district. Methodology: A quantitative associative-causal design was employed. Data were obtained through five-point Likert questionnaires from 100 purposively selected village officials, BPD members, and RT/RW community representatives from eight villages. The model was analyzed using Partial Least Squares Structural Equation Modeling in SmartPLS 4.0. Results: Village apparatus competence, community participation, and BPD supervision each had positive and significant effects on village fund management effectiveness. Community participation was the strongest predictor (path coefficient = 0.501). The three determinants explain 60.6% of the variance in effectiveness, based on the adjusted R-squared. Conclusions: Effective village fund management depends on the combined operation of administrative capacity, meaningful citizen involvement, and institutional oversight. Limitations: The evidence is limited to eight villages, three predictors, and perception-based cross-sectional data. Contributions: This study extends stewardship-based village governance research by showing that competence enables responsible action, participation supplies local information and social control, and BPD supervision provides corrective oversight. Practically, it identifies community participation as a priority lever for improving program relevance and public value. Novelty: The three governance mechanisms are tested simultaneously for effectiveness rather than just accountability using a multi-actor village sample.